Pengaruh Dana Alokasi Umum, Pendapatan Asli Daerah dan Belanja Modal Terhadap Kemandirian Keuangan Daerah Pada Pemerintah Kabupaten Bandung Tahun 2019-2023 - Putri, Annisa; Mulyandani, Vina Citra (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The level of regional financial independence (KKD) shows the ability of the regional government to reduce dependence on transfer income to finance all its government activities as a manifestation of regional autonomy. The purpose is to empirically test the influence of DAU, PAD and BM on KKD in the Bandung Regency Government in the 2019-2023. The research method is quantitative, the type of data used is secondary data, the data analysis method used descriptive statistical tests, classical assumption test, multiple linear regression and test hypotheses t and f with the help of SPSS version 26. Based on the analysis technique using multiple regression, it shows that partially the DAU has a significant effect on KKD, while the other two components, PAD and BM, do not affect KKD. Then the results of simultaneous testing show that there is no significant influence of DAU, PAD and BM on KKD.